A Randomized Controlled Trial to Test the Effectiveness of Intrauterine Balloon Tamponade with Condom Catheter in Severe Postpartum Hemorrhage Management: A Feasibility Study in Benin - TORT, JULIE; HOUNKPATIN, BENJAMIN IGNACE BODOUNRIN; POPOWSKI, THOMAS; TRAORE, MAMADOU; BODIN, CECILE; PERRIN, RENÉ-XAVIER (My University, 2013)
Background: In low-resource countries, Postpartum Hemorrhage (PPH) is the leading cause of maternal mortality. Thus, it is important to identify procedures that are adapted to their situation. The intrauterine balloon tamponade was recently incorporated into the strategy to manage uterine atony. There are many types of tamponades. Among them, the condom catheter seems to be an efficient and economic intervention for the treatment of PPH in lowresource countries. However, its effectiveness has not yet undergone rigorous evaluation. Our objective is to assess the feasibility of a Randomized Control Trial (RCT) that will test the efficacy of the intrauterine balloon tamponade with condom catheter in low-resource countries. Methods: We carried out a pilot study of an individual randomized parallel-group controlled trial (CONDOM-PPH Trial) in three health facilities representing different levels in the health pyramid in Cotonou, Benin. Women presenting postpartum hemorrhage refractory to first-line treatments after a vaginal delivery were included. The main outcomes measures were the feasibility of recruitment, acceptability of the condom catheter by clinicians, its impact on organizing care, and its tolerance among women. Data collected from interviews with clinicians, field observations, a standardized questionnaire on the women’s characteristics and their treatment at inclusion, and a weekly data-collection system on facility activities and inclusion monitoring. Analysis was performed using quantitative and qualitative methods. Results: The condom catheter is generally well accepted by clinicians. Its assembly was considered fast and easy. No side effects were reported. Over a four-month period, ten women were randomized: five in the intervention group (condom catheter + misoprostol) and five in the control group (only misoprostol). The recruitment rate was 0.3% of vaginal deliveries. Conclusion: By ensuring that measures are taken to increase staff motivation, implementing a RCT is feasible in this context despite a few technical difficulties related to randomization in an emergency situation.
Keywords: Postpartum hemorrhage; Low-resource countries; Uterine balloon tamponade; Pilot study